Barriers to Physical Activity and Healthy Eating in Children as Perceived by Low-Income Parents: A Case Study - W. Hey, David; M. Kelly, Kristina; Teaford, Stephanie; Yelmokas McDermott, Ann (International Journal of Nutrition, 2015)
During the past three decades the prevalence of childhood obesity has steadily increased in the United States. Causes of childhood obesity are complex and include numerous individual and environmental factors. The purpose of this study was to determine parent perceptions on the social-ecological barriers (community, school, and family) to physical activity and healthy eating, perceived specific to their children. Self-reported data gathered from a 50-item questionnaire and six focus groups were conducted with parents (n=43) enrolled in the Women, Infants, and Children (WIC) Program. Participants (16 to 67 years old) were predominately female (88.4%), Hispanic (67%), low income, and living in or near Lompoc in Santa Barbara County, CA. The social-ecological model (family, school, and community) was utilized to create focus group questions and provide recommendations as part of the Lompoc Community Health Improvement Project (2006-to-the-present). Popular community barriers for physical activity were: disconnected sidewalks, lack of safe bike routes to school, lack of recreational programming at an affordable cost, and language barriers (lack of marketing physical activity programs in Spanish). Two safety barriers involved parks; fear of injury (dilapidated equipment) and fear of gangs (violence). Common school barriers were: teachers do not lead-by-example, lack of healthy food in school cafeteria, and insufficient time for children to purchase food and eat. Family barriers included: grandparents sabotaging healthy eating environments (e.g., spoiling children), insufficient nutrition knowledge (both children and parents), and economics (not being able to afford healthy food and a recreation/gym membership).
Keywords: childhood obesity; focus group methodology; social-ecological framework; Women; Infants and Children (WIC) participants; parental perception